Relevance of biomarkers indicating gut damage and microbial translocation in people living with HIV - Ouyang, Jing; Yan, Jiangyu; Zhou, Xin; Isnard, Stéphane; Harypursat, Vijay; Cui, Hongjuan; Routy, Jean-Pierre; Chen, Yaokai (Frontiers in Immunology, 2023)
The intestinal barrier has the daunting task of allowing nutrient absorption while limiting the entry of microbial products into the systemic circulation. HIV infection disrupts the intestinal barrier and increases intestinal permeability, leading to microbial product translocation. Convergent evidence has shown that gut damage and an enhanced level of microbial translocation contribute to the enhanced immune activation, the risk of non-AIDS comorbidity, and mortality in people living with HIV (PLWH). Gut biopsy procedures are invasive, and are not appropriate or feasible in large populations, even though they are the gold standard for intestinal barrier investigation. Thus, validated biomarkers that measure the degree of intestinal barrier damage and microbial translocation are needed in PLWH. Hematological biomarkers represent an objective indication of specific medical conditions and/or their severity, and should be able to be measured accurately and reproducibly via easily available and standardized blood tests. Several plasma biomarkers of intestinal damage, i.e., intestinal fatty acid-binding protein (I-FABP), zonulin, and regenerating islet-derived protein-3α (REG3α), and biomarkers of microbial translocation, such as lipopolysaccharide (LPS) and (1,3)-β-D-Glucan (BDG) have been used as markers of risk for developing non-AIDS comorbidities in cross sectional analyses and clinical trials, including those aiming at repair of gut damage. In this review, we critically discuss the value of different biomarkers for the estimation of gut permeability levels, paving the way towards developing validated diagnostic and therapeutic strategies to repair gut epithelial damage and to improve overall disease outcomes in PLWH.